Prevalence of unwanted pregnancy in Iranian women: a systematic review and meta-analysis - Rostam Jalali; Masoud Mohammadi; Aliakbar Vaisi-Raygani; Akram Ghobadi; Nader Salari (BMC, 2019)
Abstract Background Unwanted pregnancies are considered as one of the most important public health risks. Regarding the importance of the unwanted pregnancy in the country and helping health policy-makers obtain more accurate information on this issue, this study aims to provide a systematic review and meta-analytical on the prevalence of unwanted pregnancies in Iran. Methods The present study was carried out using meta-analysis. Articles related to the topic were obtained through SID, Magiran, Scopus, PubMed, and ScienceDirect and Google Scholar databases from 2001 to 2017, Articles written based on cross-sectional studies were included in the study and other overviews, case-control, cohort, and interventional studies were excluded from the list of articles. Heterogeneity of studies was investigated using I2 index and data analysis was performed in Comprehensive Meta-Analysis software (Version 3). Results In 23 articles, the prevalence of unwanted pregnancy in Iranian women was 27.9% (95%CI: 24-32.1%). The meta-regression analysis was used in two sample sizes and years of study. It was reported that as the sample size and Years increases, the prevalence of the unwanted pregnancy decrease, this difference was also statistically significant (P = 0.000). Conclusion Considering that the prevalence of unwanted pregnancy is high in Iran, it is necessary that health policy makers take effective measures to enhance the awareness of couples and public information about the risks of the unwanted pregnancy.